An Evaluative Framework of Legal Aid Models - Arthur L. Berney; Harry A. Pierce (Washington University Law Quarterly, 1975)
The purpose of this Article is to place the systems for legal service to the poor in the developed countries of the world within an evaluative perspective that may be useful to planners of such systems in developing countries. Part I presents one exposition of the process of national development, with particular emphasis on the role of law and lawyers. Part II describes the major legal service systems used in the West. In Part III, some observations are offered about the relationship between a country’s development goals and its choice of a legal service program or system.